Internal control and financial management of a food supplier company - Acosta Ruiz, Nury (2021)
Objective determine the effect of internal control on the financial management of a food supplier company in 2020. Methodology: The data collection technique was the interview, observation and documentary analysis. The techniques corresponded to the interview guide, verification sheet and document analysis guide.  Results: determined that the food supplier company has deficiencies in the internal control components; where there was evidence of a shortage of stocks, deterioration, lost merchandise and expiration, adding a total of S / 48,296.90 in losses. Likewise, after having adjusted the findings, it was determined that the company would have obtained a higher return, that is, the liquidity and profitability indicators would have been higher than what was obtained Conclusion: that internal control affects the financial management of the food supplier company.